Sistem Pendukung Keputusan Seleksi Pemilihan Perguruan Tinggi Terbaik Menggunakan Metode Topsis - La Beu, Dian Nurcahyani; Boling, Angel Agustina; Fua, Andreas Curtis Hopper; Kaesmetan, Yampi R (Universitas Stikubank, 2024)
Decision Support System (SPK) can be used to select the best college in this journal, the author uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method which is expected to be a solution for consideration for prospective new students who want to pursue higher education. From the calculation results, it is found that the highest result value from the calculation formula can be used to be the best choice in choosing a college for prospective students. With confusion matrix accuracy reaching 90%.